Kemampuan Literasi Matematis pada Pokok Bahasan Sistem Persamaan Linier Tiga Variabel melalui Problem Based Learning - Hidayat, Syafri; Hartono, Yusuf (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research is a qualitative descriptive study with the aim of describing students' mathematical literacy abilities after studying SPLTV material using the PBL model. What is new in this research is the use of the PBL model in studying SPLTV material to describe mathematical literacy abilities in each category. This research was carried out in class X.8 SMAN 1 Indralaya for the 2023/2024 academic year. Students in the high category are able to formulate problems into SPLTV form and can determine mathematical solutions from the SPLTV and can interpret mathematical results based on the question so that they are able to solve problems. Students in the medium category are able to formulate problems into SPLTV form and are quite capable of determining mathematical solutions from the SPLTV, but are not yet able to interpret them so they are not able to solve problems. Students in the low category are only able to formulate problems in the form of SPLTV and are not yet able to solve problems. Group and individual guidance, which is one of the phases in PBL, makes students interested in solving SPLTV problems using mathematical literacy skills.